2019
DOI: 10.3168/jds.2018-15445
|View full text |Cite
|
Sign up to set email alerts
|

Acute pain responses in dairy calves undergoing cornual nerve blocks with or without topical anesthetic

Abstract: Dairy calves are routinely administered medicines, vaccines, and anesthesia via injection. Although injections are painful, little is known about methods to alleviate this pain. The aim of this study was to determine whether lidocaine-prilocaine cream, a topical anesthetic, reduced calves' pain response to a subcutaneous injection around the cornual nerve. Calves were assigned 1 of 2 treatments: lidocaine-prilocaine cream at the sites of injection (n = 10) or no cream (n = 9). Thirty minutes after treatment, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
(55 reference statements)
0
15
0
1
Order By: Relevance
“…We took steps to reduce this aversiveness by buffering the lidocaine with sodium bicarbonate to decrease its acidity and by applying a topical anesthetic to numb the skin before injection. Unfortunately, we have since found that the anesthetic cream we used may worsen injection pain rather than alleviate it 19 . However, the cream was used for both lidocaine and saline injections and so cannot explain the sham calves' aversion to lidocaine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We took steps to reduce this aversiveness by buffering the lidocaine with sodium bicarbonate to decrease its acidity and by applying a topical anesthetic to numb the skin before injection. Unfortunately, we have since found that the anesthetic cream we used may worsen injection pain rather than alleviate it 19 . However, the cream was used for both lidocaine and saline injections and so cannot explain the sham calves' aversion to lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Body weights were similar among treatment groups the day before disbudding (mean ± SD; Day 0 Sham: 44 ± 6 kg; Day 0 Disbud: 45 ± 7 kg; Day 20 Sham: 43 ± 7 kg; Day 20 Disbud: 43 ± 5 kg). On the day of disbudding, the calf was restrained in a head device in her home enclosure, as previously depicted 19 . A 5 ×5 cm patch of hair was clipped with a size 40 electric razor blade on each side of the head to locate the horn bud.…”
Section: Treatmentsmentioning
confidence: 99%
“…The side (left vs. right) that each iron was applied to was alternated and balanced between calves. On the day of disbudding, the calf was restrained in a head device in her home pen (Jimenez et al, 2019) and a 5 × 5 cm patch was clipped on each side of the head to locate the horn bud. The calf received a cornual nerve block of 5 mL 2% lidocaine hydrochloride injected on each side with a 20-gauge × 25-mm needle.…”
Section: Part I: Iron Effects On Wound Healingmentioning
confidence: 99%
“…A measuring tape was placed to the right of the wound and included in the photographs to evaluate wound size. During photography, the calf was restrained and blindfolded in a head device in her home pen (Jimenez et al, 2019).…”
Section: Part I: Iron Effects On Wound Healingmentioning
confidence: 99%
“…The percentage of eye white area (ocular sclera) in the eye of cattle has been measured as an indicator of emotional state in some studies (Sandem et al 2006;Proctor and Carder 2015;Lambert and Carder 2017;Gómez et al 2018;Jimenez et al 2019) and was associated with a strong emotional response in dairy cows (Sandem and Braastad 2005). The percentage of the visible white area increases when the upper eyelid is lifted.…”
Section: Facial Expression and Emotions In Animalsmentioning
confidence: 99%